SPECIFICITY OF THE ORGANIZATION OF ATTESTATION OF MASTER OF PRODUCTION EDUCATION ON THE BASIS OF FOREIGN EXPERIENCE - Uralov Sirojiddin (Bright Mind Publishing, 2025)
This article highlights the importance of integrating, constantly changing and cooperating with employers theoretical and practical knowledge in the process of attesting masters of production education, based on foreign experience, and the fact that these approaches are an effective tool for effectively organizing the educational process and increasing the level of qualifications of masters of production education.
Keywords: The work includes advanced training courses, vocational training, certification, qualification, dual training, and a training seminar.